2018
DOI: 10.1007/s11126-018-9566-7
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effectiveness of Different Cortical Targets Used in Repetitive Transcranial Magnetic Stimulation (rTMS) for the Treatment of Obsessive-Compulsive Disorder (OCD)

Abstract: Randomised and sham-controlled trials (RCTs) of repetitive transcranial magnetic stimulation (rTMS) in the treatment of obsessive-compulsive disorder (OCD) have yielded conflicting results, which may be due to the variability in rTMS parameters used. We performed an updated systematic review and meta-analysis on the effectiveness of rTMS for the treatment of OCD and aimed to determine whether certain rTMS parameters, such as cortical target, may be associated with higher treatment effectiveness. After conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 72 publications
4
78
0
Order By: Relevance
“…While Berlim et al, (2013)identified the SMA and OFC as more promising rTMS targets for treating OCD than the DLPFC, the meta-analysis by Rehn et al, (2018)revealed that targeting the SMA yielded significant improvements in OCD symptoms, whereas active rTMS targeting the OFC was not more effective thanshamrTMS. Although studies targeting the OFC and SMA remain scarce, which limits our ability to draw conclusions, the meta-analysis by Rehn et al (2018) and our study extend existing research by clarifying the differing effectiveness of rTMS in OCD when applied over different cortical regions (Rehn et al, 2018).…”
Section: Discussion:-supporting
confidence: 58%
“…While Berlim et al, (2013)identified the SMA and OFC as more promising rTMS targets for treating OCD than the DLPFC, the meta-analysis by Rehn et al, (2018)revealed that targeting the SMA yielded significant improvements in OCD symptoms, whereas active rTMS targeting the OFC was not more effective thanshamrTMS. Although studies targeting the OFC and SMA remain scarce, which limits our ability to draw conclusions, the meta-analysis by Rehn et al (2018) and our study extend existing research by clarifying the differing effectiveness of rTMS in OCD when applied over different cortical regions (Rehn et al, 2018).…”
Section: Discussion:-supporting
confidence: 58%
“…The use of TMS has also developed since OCD treatment guidelines were last written, and new treatment guidelines will need to reconsider the role of TMS in the treatment of OCD (Lusicic, Schruers, Pallanti, & Castle, ; Rehn, Eslick, & Brakoulias, ). Defining the role of newer treatment strategies in guidelines encourages clinicians to consider such treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a significant abnormality in the influences on and by the DLPFC in patients with OCD regarding the nodes of the SMN, such as the SMA. Previous studies suggested that the SMA had increased relative activation during response inhibition ( de Wit et al, 2012 , Del Casale et al, 2011 ) and that hyperactivity of SMA was related to deficient inhibitory control, which may explain compulsions such as repetitive or ritualized behaviors in OCD patients ( Rehn et al, 2018 , Yucel et al, 2007 ). Our findings indicated that the DLPFC had an increased inhibitory influence on the SMA in patients with OCD, and the DLPFC may counteract SMA hyperactivity with feedback inhibition in OCD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The DLPFC has been the most investigated target for noninvasive neuromodulatory treatment in OCD ( Shivakumar et al, 2019 ). Evidence from recent meta-analyses indicated that repeated transcranial magnetic stimulation (rTMS) targeting the left, right, or bilateral DLPFC was significantly more effective than sham rTMS in improving OCD symptoms ( Lusicic et al, 2018 , Rehn et al, 2018 , Zhou et al, 2017 ). In addition, the activation of the DLPFC during symptom provocation tasks was negatively correlated with the response to cognitive behavioral therapy (CBT), which indicated that excessive activation of the DLPFC may hinder the response to CBT ( Olatunji et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%